Isolating Human Monoclonal Antibodies Against Adeno-Associated Virus From Donors With Pre-existing Immunity - Giles, April R.; Calcedo, Roberto; Tretiakova, Anna P.; Wilson, James M. (Frontiers in Immunology, 2020)
With the advent of single B-cell cloning technology, we can isolate antibodies against virtually any antigen to study the interaction of a given pathogen with the immune system and develop novel therapeutic strategies. Antibodies directed against the capsid of adeno-associated viruses (AAV) are a significant obstacle to effectively leveraging AAV as a gene-delivery vector in seropositive individuals. In order to design next-generation vectors that can evade neutralization by these antibodies, studies have mapped the epitopes of mouse monoclonal antibodies generated by immunization with AAV. Although these studies provide critical information regarding capsid immunogenicity, they cannot address (1) differences in the antibody repertoire generated in humans following AAV natural infection; or (2) how reactions can vary when generated in response to vector administration. Here, we isolated and evaluated a panel of novel, fully human anti-AAV antibodies by cloning single memory B cells from a seropositive normal donor. We have validated the utility of this approach to study AAV immunology. Our goal is to leverage this knowledge to design novel AAV variants that can effectively transduce target tissues in individuals with AAV-neutralizing antibodies.